Analisis Perencanaan Budgetting Dalam Mengoptimalkan Diklat - Madaniyah, Madaniyah; Rohadi, Rohadi; Safaruddin, Safaruddin; Afriza, Afriza (Pascasarjana Institut Agama Islam Sunan Giri Ponorogo, 2024)
The aim of this research is to analyze Budgeting Planning Analysis in Optimizing Training. This type of research is a library study. Data collection with documentation. Data analysis with SLR. Research results Effective budget planning is very important in optimizing the implementation of training (education and training) in an organization. By planning the budget appropriately, organizations can ensure efficient allocation of funds for training activities, so that the goal of developing participant competency can be achieved optimally. A good budgeting process also allows for easier evaluation of the achievements and impact of the training activities. Therefore, a mature management budget is a key factor in improving the quality and desirability of the training programs being held.